2018
DOI: 10.1093/infdis/jix656
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Treatment Duration in Patients With Chronic Delta Hepatitis and its Effect on the Natural Course of the Disease

Abstract: Viral response to interferon increases with treatment duration and favorably affects the natural course of disease. Interferon treatment duration has to be individualized with careful post-treatment assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
100
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 41 publications
8
100
0
4
Order By: Relevance
“…Treatment response is observed in around 25%‐40% after 1 year of treatment and extending treatment to 2 years does not appear to increase response rates . Still, there are data to suggest that IFN may need to be given for an extended duration of time, which is consistent with in vitro studies that appear to lend support for longer treatment duration . Viral kinetic studies also support the concept that CDH responds slower to IFN compared to hepatitis B (HBV) or hepatitis C virus (HCV) …”
mentioning
confidence: 58%
“…Treatment response is observed in around 25%‐40% after 1 year of treatment and extending treatment to 2 years does not appear to increase response rates . Still, there are data to suggest that IFN may need to be given for an extended duration of time, which is consistent with in vitro studies that appear to lend support for longer treatment duration . Viral kinetic studies also support the concept that CDH responds slower to IFN compared to hepatitis B (HBV) or hepatitis C virus (HCV) …”
mentioning
confidence: 58%
“…In several studies, a variable percentage of patients ranging from 17% to 47% achieved undetectable HDV‐RNA levels by the end of treatment . Many of these patients relapsed during follow‐up; hence, the overall response was suboptimal . In addition, interferon has important adverse effects and contraindications that limit its use .…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been performed with the hypothesis that two years of treatment would be superior to one, but these did not yield the anticipated results. Meanwhile, expert opinions and certain case presentations and some previous studies suggested that that some patients might be benefit from long-term treatment (30)(31)(32)(33). In a retrospective study focusing on the delta hepatitis database of Ankara University School of Medicine, increasing the duration of treatment was shown to increase cumulative treatment response rates as well (33).…”
Section: Treatment Patients With Cdhmentioning
confidence: 97%
“…Patients who respond to treatment have lower rates of developing cirrhosis, lower need to LT and lower hepatic diseaserelated mortality compared to those who do not respond (33).…”
Section: Treatment Patients With Cdhmentioning
confidence: 99%
See 1 more Smart Citation